1970
DOI: 10.4141/cjps70-129
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Seeding Dates, Seeding Rates, and Fertilizers on Two Cultivars of Barley

Abstract: Two commercially suitable barley cultivars yields from seeding rates were not differenwere compared for three years at different tially afiected by fertilizer treatments. The dates and iates of seeding and fertility levels. seeding rate of 67 ke/ha, considerably, below Conquest was significantly higher in yield the average used in practice, gave th.e_highest than-Olli and the differential magnitude in-yields. There were no significant differences creased as seeding was delayed. Olli matured in unit volume or k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…Spring grain yields were significantly reduced with later planting dates which agrees with previously reported results in other regions of North America (1,4,5,7,8,10,11,13). However, the significant cultivar X seeding date and cultivar X seeding date X year interactions for grain yield indicate the need to examine new cultivars under various seeding dates.…”
Section: Discussionsupporting
confidence: 89%
“…Spring grain yields were significantly reduced with later planting dates which agrees with previously reported results in other regions of North America (1,4,5,7,8,10,11,13). However, the significant cultivar X seeding date and cultivar X seeding date X year interactions for grain yield indicate the need to examine new cultivars under various seeding dates.…”
Section: Discussionsupporting
confidence: 89%
“…Delayed seeding reduced grain yield at all but one site in this study, consistent with previous reports (Beard 1961;McFadden 1970;Ciha 1983;Lauer and Partridge 1990;Juskiw and Helm 2003). The average yield loss of 20% at the latest seeding in this study was less than observed in Minnesota (35%, Beard 1961) and central Alberta (47%, Juskiw and Helms 2003), likely due to the shorter time period between the first and last seeding dates in this study (≈ 3 wk) than in the latter studies (5 to 6 wk).…”
Section: Seeding Datesupporting
confidence: 93%
“…Typically, the highest grain yields are achieved with the earliest feasible seeding date, with initially a gradual decline, then a much more rapid decline when seeding is delayed (Beard 1961;McFadden 1970;Ciha 1983;Lauer and Partridge 1990;Juskiw and Helm 2003). The impact of delayed seeding on grain yield varies among years and cultivars (Ciha 1983;Juskiw and Helm 2003).…”
mentioning
confidence: 99%
“…Planting date and N fertilizer significantly affect spring barley grain yield, grain protein and kernel plumpness (9,17). Delayed planting decreases barley grain yield and kernel plumpness (12) while increasing grain protein (3,9,17). Insufficient N can reduce grain yield and quality below acceptable levels, while excessive N usually produces undesirable high protein levels (1,14).…”
mentioning
confidence: 99%